DAMPAK PENAMBANGAN GALIAN TANAH TERHADAP TINGKAT PRODUKSI PERTANIAN TANAMAN PADI DI KECAMATAN NALUMSARI KABUPATEN JEPARA - Khoirun, Amin Muhammad (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2014)
The purpose of this study to determine the impact of mining excavation to theagricultural production level of rice plants. The population in this study was arice farm land after the mining excavation in District Nalumsari. Data collectionmethods used were observation, interviews and literature studies. EngineeringAnalysis using descriptive analysis and laboratory methods. The results showedthat the level of agricultural production of rice plants before any excavationmining activities in the district of Jepara regency Nalumsari average of 8.91tonnes / acres / year, while the mining excavation after an average of 7.87 tonnes/ acres / year after 2012 in a year produces two harvests. Suggestions arenecessary to provide additional information to farmers so that they could bebetter understand the negative impacts of soil excavation and to provideeducation about effective conservation methods to an ex-mined land.